High efficiency organic solar cells based on amorphous electron-donating polymer and modified fullerene acceptor. (September 2017) - Xiao, Biao; Zhang, Minli; Yan, Jun; Luo, Guoping; Gao, Ke; Liu, Jiyan; You, Qingliang; Wang, Hong-Bo; Gao, Chao; Zhao, Baofeng; Zhao, Xuebo; Wu, Hongbin; et al.
Abstract: The current manuscript examines the structure and property relationship of amorphous conjugated polymer based bulk heterojunction solar cells. Solvent vapor annealing (SVA) is used to optimize the morphology. It is seen that the structure order of the blended thin film does not change but phase separation becomes prominent. The space charge limited current and admittance spectroscopy reveals that the charge transport ability of the SVA-treated device is significantly strengthened. Furthermore, both the current-voltage analysis and impedance spectroscopy illustrates that SVA can effectively promote the fill factor (FF) and short circuit current density ( J sc ) due to the enhanced charge transport properties. However, the increased mobility after the SVA treatment causes non-geminate charge carrier recombination and reduces geminate recombinations. In particular, the reduction in open circuit voltage ( V oc ) of the solvent vapor annealed devices is found to originate from the charge recombination induced by the quasi-Fermi level variation between the donor and acceptor materials. Graphical abstract: Highlights: Amorphous polymer is used as electron-donating material in high performance bulk heterojunction organic solar cells. In-chain charge transport will help to reappraise the charge transport mechanism in organic semiconductors. The improved charge carrier mobility of both holes and electrons are the major reason for the fill factor increase. The carrier recombination during the SVA processing induces a loss in device open circuit voltage. The carrier dynamics is well illustrated by impedance spectroscopy and capacitance-voltage measurement.